The Role of Religion in Constructing Ethnic Identity: The Case of Danu Son See Yar Day, a Religious-based Cultural Festival in Myanmar - Javansami, Ven. (Journal of International Buddhist Studies, 2020)
This article explores the importance of religion and ethnic cultural performance in building the ethnic identity of the Danu people. Danu is a considerably large ethnic group in southern Shan State, Myanmar. However, until they started to organize the Danu Son See Yar Day (the DSSYD), a cultural festival based on Buddhism, their ethnic identity was unknown to the country. The invisibility of Danu ethnic identity is due to the lack of connection and unity between them. To answer the question of what is the role of religion and culture in the construction of Danu ethnic identity, I conducted this research by participating in the festival and interviewing some cultural informants who know this subject well. The result shows that by giving the opportunity to conduct religious and ethnic cultural affairs, this festival paved the way for a large gathering of Danu people which allowed them to become connected and united. More importantly, it became an essential event not only for the development of the Danu ethnic community itself, but also in maintaining harmony between them with other ethnicities through religious and cultural exchanges.